Global governance: the G20 and a Global Green New Deal - Edward B. Barbier (Kiel Institute for the World Economy (IfW), 2009)
In response to the world economic crisis, the international community should promote a mix of policies to sustain global recovery and create jobs through reducing carbon dependency, ecological degradation and poverty. Such a Global Green New Deal (GGND) requires implementation and coordination of green investments by the Group of 20 (G20), who should also adopt complementary pricing policies and foster international aid and other actions in support of the GGND. Developing economies should provide clean water and sanitation for the poor, create safety nets, invest in heath and education, and target energy and water poverty. Such a global strategy can revive economies, create jobs and improve the sustainability of world development.
Keywords: F55; F59; H87; O13; O19; Q01; Economic Recession; G20; global governance; Global Green New Deal; green stimulus; low-carbon economy; world economy